Effect of miR-1285-3p as a diagnostic biomarker for chronic heart failure on vascular endothelial cells - Chongyang Zhang; Jiazhen He; Dan Xiong; Yi Mei; Yao Zhu; Pan Deng; Yang Duan (Journal of Cardiothoracic Surgery)
Abstract Background MicroRNAs (miRNAs) are closely related to cardiovascular diseases, including chronic heart failure (CHF). Endothelial dysfunction can lead to heart failure. The purpose of this study was to evaluate the clinical significance of miR-1285-3p in CHF patients, with the aim of identifying a novel and effective biomarker for CHF. At the same time, we investigated the effect of miR-1285-3p on vascular endothelial cells. Methods Total RNA was extracted from plasma samples of 106 CHF patients and 106 healthy individuals. Quantitative Real-time PCR (qRT-PCR) was used to detect the expression of miR-1285-3p. The diagnostic accuracy of miR-1285-3p was tested by receiver operating characteristic (ROC) curve. Evaluated the related risk factors of CHF using logistic analysis. The proliferation and apoptosis of human umbilical vein endothelial cells (HUVECs) were detected by transfecting miR-1285-3p mimic or miR-1285-3p inhibitor in vitro using CCK8 and flow cytometry. Effect of miR-1285-3p on the angiogenesis of HUVECs were detected by in vitro angiogenesis assay. Results miR-1285-3p is upregulated in CHF patients, demonstrating the ability to distinguish CHF patients from healthy individuals, with high sensitivity (83.0%) and specificity (93.4%). In vitro experiments revealed that transfection of miR-1285-3p mimic inhibited endothelial cell proliferation, accelerated apoptosis, and inhibited endothelial cell angiogenesis, which was reversed by transfection with miR-1285-3p inhibitor. Conclusion miR-1285-3p is upregulated in CHF and may serve as a new effective biomarker for CHF diagnosis, which can inhibit HUVECs angiogenesis.